(untitled) (Journal of the College of Basic Education, 2022)
Nowadays, smartphones have become very famous and are deemed as the foremost communication device in the world. These light and small devices enable their users to transit from one network to another quite easily. Furthermore, mobile-devices decrease the processing data cost besides the time of execution in order to achieve rapid outcomes. Because of these characteristics, novel conceptions in education and industry are emerging, such as BYOD “Bring Your Own Device”. This conception, which is quite new, seeks to utilize personal devices as work elements and will support industry to incorporate a lot of applications on mobiles .This leads to, making the organizations less reliant on desktop execution-power and create more productive employers through smooth deployment operations that can be applied anytime and anywhere at a low cost.